1998
DOI: 10.1021/cm980494n
|View full text |Cite
|
Sign up to set email alerts
|

Free Radical Induced Acceleration of Cationic Photopolymerization

Abstract: Two new monomers based on R-terpineol were prepared, allyl R-terpineol ether epoxide (III) and 1-propenyl ether R-terpineol epoxide (IV). The photoinitiated cationic polymerizations of these two monomers as well as two model compounds, 1-propenyl R-terpineol ether and methyl R-terpineol ether epoxide, were studied using real-time infrared spectroscopy. Surprisingly, the rates of epoxide ring-opening polymerization of both monomers were greatly enhanced as compared to the model compounds. At the same time, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 66 publications
(35 citation statements)
references
References 17 publications
0
35
0
Order By: Relevance
“…We call such compounds hybrid monomers. In three recent papers, [7][8][9] we reported that cycloaliphatic epoxy monomers bearing 1-propenyl ether groups with the structures shown below undergo photoinduced cationic epoxide ring-opening polymerization at anomalously high rates.…”
Section: Introductionmentioning
confidence: 99%
“…We call such compounds hybrid monomers. In three recent papers, [7][8][9] we reported that cycloaliphatic epoxy monomers bearing 1-propenyl ether groups with the structures shown below undergo photoinduced cationic epoxide ring-opening polymerization at anomalously high rates.…”
Section: Introductionmentioning
confidence: 99%
“…Diaryliodonium salts are oxidants with low reduction potentials. Several research groups30–35 have taken advantage of this fact by using easily oxidized free radicals generated by both Norrish Type I and II photoreactions to generate a cationic initiating species by the chemical reduction of a diaryliodonium salt. For example, unimolecular free radical photoinitiators such as 2,2‐dimethoxy‐2‐phenylacetophenone (Irgacure 651) undergo efficient photolysis by a Norrish I type α‐cleavage reaction as shown in eq 9 of Scheme to afford the benzoyl ( VI ) and dimethoxyphenylmethyl radicals ( VII ).…”
Section: Resultsmentioning
confidence: 99%
“…[12][13][14] The self-sustaining propagation of the FP toward the formulation thickness is ensured by thermal decomposition www.advancedsciencenews.com www.mcp-journal.de kept at high vacuum (about 0.03 mbar) for at least 3 h until bubble formation had ceased. The apparatus developed by Bomze et al was used for the RICFP setup.…”
Section: Introductionmentioning
confidence: 99%